2004
DOI: 10.2174/0929867043365297
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Superoxide Dismutase: A Promising Target for New Anticancer Therapies

Abstract: Compelling experimental and epidemiological evidence involves oxygen radicals in carcinogenesis, acting reactive oxygen species both as endogenous genotoxins during cell initiation and as messenger molecules in mitogenesis and in tumor promotion. Moreover, oxidants stimulate neoangiogenesis, which is a prerequisite for tumor growth. However, while several natural as well as synthetic antioxidant compounds appear to be chemopreventive in mutagenicity assays, antioxidant-based treatments for the prevention or cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 85 publications
(109 reference statements)
2
57
0
1
Order By: Relevance
“…As our new data support the involvement of both pathways in POX-induced apoptosis, whether ROS/superoxides participate in both processes became an important question. Our strategy, similar to our previous study (Liu et al, 2005), is to hyperexpress manganese superoxide dismutase (MnSOD), an antioxidant enzyme, which decomposes superoxide radicals to hydrogen peroxide and has been reported to inhibit apoptosis induced by a variety of agents (Pani et al, 2004). Importantly, we found that MnSOD blocked the cleavage/activation not only of caspase-9 and 3, but also caspase-8, the identifying caspase of the death receptor pathway (Figure 3b).…”
Section: Manganese Superoxide Dismutase Abrogation Of Poxinduced Apopsupporting
confidence: 68%
“…As our new data support the involvement of both pathways in POX-induced apoptosis, whether ROS/superoxides participate in both processes became an important question. Our strategy, similar to our previous study (Liu et al, 2005), is to hyperexpress manganese superoxide dismutase (MnSOD), an antioxidant enzyme, which decomposes superoxide radicals to hydrogen peroxide and has been reported to inhibit apoptosis induced by a variety of agents (Pani et al, 2004). Importantly, we found that MnSOD blocked the cleavage/activation not only of caspase-9 and 3, but also caspase-8, the identifying caspase of the death receptor pathway (Figure 3b).…”
Section: Manganese Superoxide Dismutase Abrogation Of Poxinduced Apopsupporting
confidence: 68%
“…25 Evidently, such an antioxidant imbalance obtained by upregulation of MnSOD was also recently postulated to contribute to its potential tumor suppressive function. 88 Furthermore, similar to other pathways induced by p53, there appears to exist a reciprocal downregulation of p53 and MnSOD gene expression leading to a fine tuning of p53 activity. 90 Although this gene repression was associated with reduced promoter activity in both cases, exactly how p53 and MnSOD affect each other's expression remains to be elucidated.…”
Section: P53 and The Oxidative Stress Responsementioning
confidence: 89%
“…Several apoptosis systems induced for example by death receptor ligands, IR, anti-cancer drugs and of course oxidative stress were efficiently counteracted by mitochondrial MnSOD, 88 another antioxidant enzyme regulated by p53. 25 Based on these and many other reports clearly validating MnSOD as a negative modulator of cellular apoptosis and hence, as a survival factor for cancer cells, it was postulated that pharmacological inhibition of MnSOD may represent an effective strategy to selectively kill cancer cells.…”
Section: P53 and The Oxidative Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…64 A consequence of enhanced glucose consumption is the production of reducing potential in the form of NADPH (reduced Nicotinamide Adenine Dinucleotide Phosphate) provided by upregulation of glucose-6-phosphate dehydrogenase and increased pentose phosphate pathway (PPP) activity. 69 The observation that tumor cells under constitutive oxidative stress express high levels of antioxidant enzymes 70,71 suggests that tumor cells require the upregulation of the antioxidant systems to maintain viability and proliferation. The glycolytic switch could fit an elevated requirement for fuelling the main intracellular antioxidant systems with reducing equivalents.…”
Section: Cancer Cell Energetics and Glycolysismentioning
confidence: 99%